2019
DOI: 10.1111/jfs.12738
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and genetic diversity of ESBL producing Klebsiella species isolated from livestock and livestock products

Abstract: Klebsiella species have been at the center of attention over the recent years due to its role in the evolution of antimicrobial resistance and is not only associated with nosocomial but also with food related infections worldwide. In this study, out of 336 samples of animal intestinal and foods of animal origin screened, 99 samples were found to harbor Klebsiella spp. Out of 99 isolates, 89 were Klebsiella pneumoniae and 10 were found to be Klebsiella oxytoca by mPCR. The isolates were subjected to antibiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…3) by PCR. In a study conducted by Bobbadi et al (2020) in Andhra Pradesh, 90 per cent of K. pneumoniae isolates were confirmed by PCR targeting rpoB gene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) by PCR. In a study conducted by Bobbadi et al (2020) in Andhra Pradesh, 90 per cent of K. pneumoniae isolates were confirmed by PCR targeting rpoB gene.…”
Section: Resultsmentioning
confidence: 99%
“…The isolates were further subjected to molecular confirmation by polymerase chain reaction (PCR) targeting rpoB gene for K. pneumoniae (Bobbadi et al, 2020) and invA gene for Salmonella spp. (Amini et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, we did not detect bla SHV . The dissemination of bla CTX-M-2 among K. oxytoca isolates collected from pigs has been reported [21,22], and bla CTX-M-15 and bla TEM-1 were detected in K. oxytoca isolates collected from six provinces in China [23]. K. oxytoca isolates harboring bla CTX-M were highly susceptible to cefotaxime, ceftazidime, and cefepime (93.1-98.3%) and 100% susceptible to ceftriaxone.…”
Section: Discussionmentioning
confidence: 99%
“…The ERIC-PCR-based fingerprinting method has been used for the relatedness or differentiation analysis of pathogenic bacteria, including K. pneumoniae [ 55 ]. For instance, Zhang et al [ 41 ] reported 60 ERIC genotypes among 61 K. pneumoniae strains from 1200 retail foods sampled from May 2013 to April 2014 in China [ 41 ].…”
Section: Discussionmentioning
confidence: 99%